Reassessment of the University of Alcalá Herbarium (Madrid) reveals hidden diversity of the myxomycete genus Lycogala in Spain - Leontyev, Dmytro; Moreno, Gabriel; López-Villalba, Ángela; Schnittler, Martin (Phytotaxa, 2026)
The revision of collections, held in the Herbarium of the University of Alcalá (AH) reveals 94 specimens of the myxomycete genus Lycogala, mainly from Spain, but also from Mexico (3 specimens) and France (1). Morphological identification, based on recently developed criteria, allowed identification of 14 Lycogala species, 10 of which are new to Spain, further two are new for Mexico. All species found in Spain were already known from Europe, with the single exception of L. cf. nigroconfusum. The collections of L. paraconfusum and L. guttatum in Mexico represent the first records for the whole of North America. Due to the age of collections, the molecular identification was possible only for nine specimens, thus confirming the identification of three species. To provide reference material for further studies, representative specimens of all taxa were photographed, and the barcoding sequences were submitted to NCBI GenBank.